Can physical exercise modify intestinal integrity and gut microbiota composition? A systematic review of in vivo studies - Santana Pereira, Stephanie Michelin; de São José, Vinícius Parzanini Brilhante; da Silva, Alessandra; Martins, Karina Vitoria Cipriana; Leite, Luciano Bernardes; Forte, Pedro; Natali, Antônio José; Martino, Hércia Stampini Duarte; Lucia, Ceres Mattos Della; Bressan, Josefina (Biology of Sport, 2025)
There is little evidence about how physical exercise affects the gut microbiota since studies in the field are relatively recent. Thus, we aimed to systematically review the main effects of regular physical exercise on the intestinal integrity and microbiota composition in animal models, discuss the mechanisms involved, and indicate future directions. Searches for original articles were performed in PubMed/MEDLINE, Scopus, Web of Science, and Embase. A total of 18 studies were selected. These studies suggest that physical exercise has a significant impact on the gut microbiota. Voluntary running increased the thickness of duodenal villi and microbiota diversity but reduced its richness. Low-intensity treadmill running increased the abundance of the phylum Actinobacteria and the family Bifidobacteriaceae, while that of moderate-intensity reduced the Bacteroides/Prevotella ratio. High-intensity swimming and treadmill running altered the gut microbiota, evidenced by β diversity, and increased the Shannon and Chao indices but reduced short-chain fatty acids. Resistance exercise increased the Chao index and altered the functionality of the gut microbiota, increasing carbohydrate metabolism and reducing lipid and amino acid metabolism. Thus, regular physical exercise of different intensities and types can modify the gut microbiota, and the exercise benefits appear to be positively associated with training intensity.